Artificial Intelligence leadership : how trust and fairness perceptions impact turnover intentions through psychological safety - Moreira, Patrícia Roque (2020)
Artificial intelligence agent’s intervention in decision making at organizational environments has been increasing rapidly. These agents bring advantages in decision making due to their objectivity, efficiency, and superior capacity of information processing while lacking human weaknesses such as fatigue or self-interest. However, their perception by organizational employees might be less optimistic, as artificial intelligence leaders might be perceived as less fair and just. This dissertation intends to study the effects that this new type of leadership has on employees' turnover intentions, an important variable as high levels of voluntary turnover cause several losses for companies both in terms of cost increase and loss of talented human resources. Additionally, I propose the decrease in employee’s psychological safety to mediate this relationship. Finally, I propose a way to overcome this effect by manipulating the perceptions of trust and justice of these leaders, in order to try to counter the negative effect of non-human leadership. The results of this study revealed a significant effect of the leader agent on the employees' exit intentions as well as on their psychological safety, including as a mediator of the former. Regarding the moderation of trust and justice perceptions, the results showed that these testimonials have a direct effect on psychological safety, and an indirect one in turnover intentions through psychological safety.